(untitled) (Bangladesh Journal of Botany, 2022)
Forty-six genotypes were subjected to genetic diversity studies for seed yield and its component characters using Mahalanobis’s D2 statistic. The analysis of variance indicated significant differences among 46 genotypes for all the 14 characters. Forty-six genotypes were grouped into nine clusters, out of which cluster-II had the maximum number of genotypes (16), followed by cluster-III (10), cluster-I (9) and cluster- IV (6). The rest of the clusters i.e. cluster-V, VI, VII, VIII and IX, each possessed single genotype. The intercluster distances surpassed the intra-cluster distances, expressing existence of stupendous diversity among the entries. The cluster-III and IV have the greatest diversity among their genotypic groups consequently these genotypes can potentially be utilized in varietal development programmes. Highest inter-cluster distance was noted between cluster-IV and VII followed by cluster-VII and VIII, and cluster-VI and VII, indicating ample of diversity available among them, Therefore, the genotypes of these clusters can be used as parents for crossing in hybridization programme to obtain desirable and excellent segregants. Protein content was the greatest contributor towards genetic divergence followed by number of clusters per plant and number of pods per cluster, suggesting direct selection of these characters. Bangladesh J. Bot. 51(2): 223-228, 2022 (June)